The Accursed Share / An Essay on General Economy: Volume I Consumption - Bataille Georges (Zone Books, 1991)
An incisive inquiry into the very nature of civilization. Preface, Theoretical Introduction, The Meaning of General Economy, Laws of General Economy, The Historical Data I, Sacrifices and Wars of the Aztecs, The Gift of Rivalry: ''Potlach'', The Historical Data II, The Conquering Society: Islam, The Unarmed Society: Lamaism, The Historical Data III, The Origins of Capitalism and the Reformation, The Bourgeois World, The Present Data, Soviet Industrialization, The Marshall Plan, Notes.